COMPARATIVE STUDY ON THE EFFICIENCY OF ROTARY VERSUS MANUAL INSTRUMENTS IN REMOVING THE ROOT CANAL FILLING - Silvia Andreea Boboc; Marius Preda; Andreea Băcioiu; Stelian Mihai Sever Petrescu; Adina Turcu; Ionela Teodora Dascălu; Ruxandra Voinea Georgescu; Mihaela Jana Țuculină (Romanian Society of Oral Rehabilitation, 2020)
The aim of this study is to evaluate the effectiveness of two techniques for removing the root canal filling: manual and rotary techniques. Material and method: The removal of root canal filling by manual technique used Kerr and Hedström files and the rotary technique used the ProTaper system. 34 extracted monoradicular teeth were used in this study. Those teeth were divided in two groups and sealed with gutta-percha and AH Plus paste (Dentsply, Maillefer). It was analyzed: the total retreatment time, the amount of apical extruded material, the radiological efficiency of the retreatment and the number of fractured instruments during the procedure. Results: It has been observed that the ProTaper rotary system removes material from the root canal much faster than hand tools. Based on the information obtained from this study, both techniques for reapplying endodontic treatment left remnants of filling material on the walls of the root canals. The amount of extruded material was significantly lower in the rotary instrumented batch. It was noted that in the case of fractured instruments, they appeared only during the manual retreatment technique. In conclusion, the ProTaper system is much more effective in retreatments than manual files.